A new hybrid method for mutual coupling minimization of an antenna array - Sara Said; Meryem Grari; Yassmina Guetbach; Abdenacer Es-Salhi; Zoheir Cif Allah; Baghaz Elhadi; Ahmed Faize (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this paper, a simultaneous application of geometric modification on patch elements and electromagnetic band gap (EBG) electromagnetic bandgap structures (hybrid method) has been suggested for 3.5 GHz wireless communication applications, to minimize the mutual coupling between radiating elements of microstrip array antennas. The suggested EBG slotted structure is composed of a one square ring and three squares placed on Rogers RO3010 having 10.2 and h=1.27 mm which presents respectively its dielectric constant and thickness. In this approach, the patch elements are geometrically modified, while also employing EBG structures, formed by four EBG cells, placed between the array elements at a near distance. The modification of the geometry of the antenna and the introduction of EBG reduces the mutual coupling of an array antenna with approximately 33 dB on the one hand and improves the antenna gain by approximately 0.43 dB on the other hand. Initially, slots are introduced in the patch geometry and then four EBG unit cells are inserted between two patches, operating at 3.5 GHz. The antenna array design parameters were optimized.